Ethephon Stimulation and Yield Response of Some Hevea Clones in the Humid Forests of South West Cameroon - J. N. Njukeng; P. M. Muenyi; B. K. Ngane; E. E. Ehabe (International Journal of Agronomy)
Several exploitation systems are being used today to sustainably improve dry rubber production by the rubber tree (Hevea brasiliensis). These involve different combinations of tapping frequencies, cut lengths, stimulation frequencies, and stimulant concentrations. Such combinations are much easier to ascertain for confirmed clones as opposed to new introductions, for which extensive testing is required. A study was therefore conducted in the South West region of Cameroon characterized by a monomodal rainfall regime (one dry and one rainy season) to evaluate yield response to Ethephon stimulation (conc. 2.5%) of some newly introduced rubber clones (IRCA 18, IRCA 19, RRIC 100, and RRIC 110) for large-scale planting in Cameroon. Generally, annual yields and tree productivity ranged between the referenced clones tested: some closer to the intermediate yielding GT 1 (IRCA 18 and IRCA 19) and others to the high yielding PB clones (RRIC 100 and RRIC 110) indicating thereby the possible convenient adoption of some established exploitation regimes for these new introductions. Climatic factors like cumulative rainfall and relative humidity conditioned rubber yields of clones tested and considerably accounted for yield variations. These results could be used as a first step towards deriving regional climate models for predicting rubber yields, especially in an era of global climate change.